2016
DOI: 10.5847/wjem.j.1920-8642.2016.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and fetal outcomes in term premature rupture of membrane

Abstract: Women residing in rural areas, long latency, and neonates with birth weight less 2 500 g may have unfavorable outcomes. Therefore, optimum obstetric and medical care is essential for the reduction of the devastating complications related to disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
41
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 18 publications
(18 reference statements)
9
41
2
1
Order By: Relevance
“…18,22,32 The higher percentage of fetal death in the current study may be attributed to high rate of low birth weight (LBW) (79.3%) and consequently high incidence of Respiratory Distress Syndrome (RDS). However, this rate is low if compared to 19 In the current study, 47% of infants were admitted to NICU which is low as compared to 65.3% and 75.8% in other studies. 32,35 The higher rate of admission compared to the current study was described as their studies were performed on preterm babies; therefore more problems and higher rate of NICU admission compared to present study that included infants born at a wider range of gestational ages.…”
Section: Methodscontrasting
confidence: 77%
See 1 more Smart Citation
“…18,22,32 The higher percentage of fetal death in the current study may be attributed to high rate of low birth weight (LBW) (79.3%) and consequently high incidence of Respiratory Distress Syndrome (RDS). However, this rate is low if compared to 19 In the current study, 47% of infants were admitted to NICU which is low as compared to 65.3% and 75.8% in other studies. 32,35 The higher rate of admission compared to the current study was described as their studies were performed on preterm babies; therefore more problems and higher rate of NICU admission compared to present study that included infants born at a wider range of gestational ages.…”
Section: Methodscontrasting
confidence: 77%
“…Obstetric data: (gravidity, gestational age at PPROM in weeks, previous history of PPROM, gestational age at delivery in weeks, type of pregnancy (single, twins, triple…), type of PPROM, latency period and history of chronic diseases of pregnant women. Maternal outcomes: Mode of delivery (spontaneous vaginal or CS delivery), presence of clinical chorioamnionitis which is characterized by maternal fever (>39˚c) accompanied by at least two of the following signs: maternal or fetal tachycardia, maternal leukocytosis, uterine tenderness, or foulsmelling amniotic fluid [19]. Fetal/Neonatal outcome: Birth weight (in Kgs), alive and well, alive but needed Neonatal intensive care unit (NICU) admission, neonatal death or others (eg., neonatal infection-jaundice).…”
Section: Methodsmentioning
confidence: 99%
“…Different studies revealed that premature rupture of membrane significantly related to increased risk of maternal, fetal and neonatal morbidities and mortalities resulting from obstetric complications. 20,21 Women with reduced fetal movement during pregnancy showed almost six-times increased odds of NNM, as compared to mothers who did not perceive reduced fetal movement. This might be due to fetal compromise, utero-placental insufficiency, intrauterine growth restriction, and/or abnormal amniotic fluid volume.…”
Section: Discussionmentioning
confidence: 99%
“…Premature rupture of either preterm or prolonged fetus is very dangerous for both mother and fetus because it is one of the factors causing asphyxia neonatorum and infection (Endale, Fentahun, Gemada and Hussen, 2016). Feffixia neonaturum occurs due to the interruption of oxygen transported from mother to fetus so that there is disturbance in the supply of 02 and in removing CO2 (Hofmeyr, GJ, et al (2008).…”
Section: Introductionmentioning
confidence: 99%